Does Information Disclosed in "Use of Proceeds" from Prospectuses Affect IPO Initial Underpricing?. (4th January 2023) - Tang, Wenxiu; Zhou, Zhong‐Guo
Abstract: We study the impact of intended use of proceeds disclosed in the section of "Use of Proceeds" in prospectuses on ChiNext IPOs' initial underpricing. After splitting the entire period into two non‐overlapping sub‐periods to control for regulatory changes and after controlling for the firm‐level characteristics and market conditions, we find that the overall information disclosed from "Use of Proceeds" affects IPO initial underpricing significantly over the two sub‐periods. Moreover, the intended use of IPO proceeds in several specific categories affects underpricing too. The proceeds raised for IPO firms' information platform and research and development over the second sub‐period while the proceeds to promote marketing and sales and to expand existing products over the first sub‐period are significantly and positively related to initial underpricing. The significance changes for the IPOs with the opportunity to change their use of proceeds after IPOs. We explore the causes and effects to explain our findings.